If D is the midpoint of CE, then CD must be equal to DE
Answer: C
Answer:
what
Step-by-step explanation:
what is this supposed to mean?
Answer:
The first derivative of
(r(t)=5*t^{-2}) with respect to t is
(r'(t) = -10*t^{-3}).
Step-by-step explanation:
Let be
, which can be rewritten as
. The rule of differentiation for a potential function multiplied by a constant is:
, ![\forall \,n\neq 0](https://tex.z-dn.net/?f=%5Cforall%20%5C%2Cn%5Cneq%200)
Then,
![r'(t) = (-2)\cdot 5\cdot t^{-3}](https://tex.z-dn.net/?f=r%27%28t%29%20%3D%20%28-2%29%5Ccdot%205%5Ccdot%20t%5E%7B-3%7D)
(r'(t) = -10*t^{-3})
The first derivative of
(r(t)=5*t^{-2}) with respect to t is
(r'(t) = -10*t^{-3}).